Do economic evaluation studies inform effective healthcare resource allocation in Iran? A critical review of the literature - Haghparast-Bidgoli, Hassan (BioMed Central, 2014)
To aid informed health sector decision-making, data from sufficient high quality economic evaluations must be available to policy makers. To date, no known study has analysed the quantity and quality of available Iranian economic evaluation studies. This study aimed to assess the quantity, quality and targeting of economic evaluation studies conducted in the Iranian context. The study systematically reviewed full economic evaluation studies (n = 30) published between 1999 and 2012 in international and local journals. The findings of the review indicate that although the literature on economic evaluation in Iran is growing, these evaluations were of poor quality and suffer from several major methodological flaws. Furthermore, the review reveals that economic evaluation studies have not addressed the major health problems in Iran. While the availability of evidence is no guarantee that it will be used to aid decision-making, the absence of evidence will certainly preclude its use. Considering the deficiencies in the data identified by this review, current economic evaluations cannot be a useful source of information for decision makers in Iran. To improve the quality and overall usefulness of economic evaluations we would recommend; 1) developing clear national guidelines for the conduct of economic evaluations, 2) highlighting priority areas where information from such studies would be most useful and 3) training researchers and policy makers in the calculation and use of economic evaluation data.